Video fluoroscopic techniques for the study of Oral Food Processing - Matsuo, Koichiro (Curr Opin Food Sci, 2016)
Food oral processing and pharyngeal food passage cannot be observed directly from the outside of the body without instrumental methods. Videofluoroscopy (x-ray video recording) reveals the movement of oropharyngeal anatomical structures in two dimensions. By adding a radiopaque contrast medium, the motion and shape of the food bolus can be also visualized, providing critical information about the mechanisms of eating, drinking, and swallowing. For quantitative analysis of the kinematics of oral food processing, radiopaque markers are attached to the teeth, tongue or soft palate. This approach permits kinematic analysis with a variety of textures and consistencies, both solid and liquid. Fundamental mechanisms of food oral processing are clearly observed with videofluoroscopy in lateral and anteroposterior projections.